Tuberculosis Molecular Bacterial Load Assay Reveals Early Delayed Bacterial Killing in Patients With Relapse. (19th June 2022) - Ntinginya, Nyanda Elias; Bakuli, Abhishek; Mapamba, Daniel; Sabiiti, Wilber; Kibiki, Gibson; Minja, Lilian Tina; Kuchaka, Davis; Reither, Klaus; Phillips, Patrick Peter John; Boeree, Martin Johan; Gillespie, Stephen H; Hoelscher, Michael; et al.
Abstract: Bacterial killing in patients with tuberculosis (TB) relapse was compared to that in patients achieving cure, measured by TB molecular bacterial load assay (TB-MBLA) or mycobacteria growth indicator tube (MGIT) time to positivity (TTP). TB-MBLA in 4 relapsed patients was significantly different compared to 132 cured patients after 2 weeks of treatment; MGIT TTP showed a significant difference from week 8.